Correction: Exploring the acceptability of a community-enhanced intervention to improve decision support partnership between patients with chronic kidney disease and their family caregivers. - Shena Gazaway; Rachel Wells; John Haley; Orlando M Gutiérrez; Tamara Nix-Parker; Isaac Martinez; Claretha Lyas; Katina Lang-Lindsey; Richard Knight; Ruth Crenshaw-Love; Allen Pazant; J Nicholas Odom (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0305291.].